Global diasporas : an introduction - Cohen, Robin, 1944- (- New York, NY : Routledge Taylor & Francis Group, 2022)
"Following its initial publication in 1997, Global Diasporas: An Introduction was central to the emergence of diaspora studies and quickly established itself as the leading textbook in the field. This expanded and fully-revised 25th anniversary edition adds two new chapters on incipient diasporas and diaspora engagement while carefully clarifying the changing meanings of the concept of diaspora and incorporating updated statistics and new interpretations seamlessly into the original text. The book has also been made more student-friendly with illustrations, thought-provoking questions, and guides to further reading. The book features insightful case studies and compares a wide range of diasporas, including Jewish, Armenians, Africans, Sikhs, Chinese, British, Indians, Lebanese, Afghans and Caribbean peoples. This edition also retains Cohen's rich historical and sociological descriptions and clear yet elegant writing, as well as his modified concept of 'diasporic rope' linking different features of diasporas. This updated edition of the definitive textbook in the field will be an indispensable guide for students and instructors seeking to explore the complex issues of diaspora, migration, and identity"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Refugees Ethnicity -- History